Structural Evolution of LixNiyMnzCo1-y-zO2 Cathode Materials during High-Rate Charge and Discharge - Hwang, Sooyeon; Jo, Eunmi; Chung, Kyung Yoon; Hwang, Kyo Seon; Kim, Seung Min; Chang, Wonyoung (American Chemical Society, 2017)
Ni-rich lithium transition metal oxides have received significant attention due to their high capacities and rate capabilities determined via theoretical calculations. Although the structural properties of these materials are strongly correlated with the electrochemical performance, their structural stability during the high-rate electrochemical reactions has not been fully evaluated yet. In this work, transmission electron microscopy is used to investigate the crystallographic and electronic structural modifications of Ni-based cathode materials at a high charge/discharge rate of 10 C. It is found that the high-rate electrochemical reactions induce structural inhomogeneity near the surface of Ni-rich cathode materials, which limits Li transport and reduces their capacities. This study establishes a correlation between the high-rate electrochemical performance of the Ni-based materials and their structural evolution, which can provide profound insights for designing novel cathode materials having both high energy and power densities.